A construção da identidade de Amaranta, personagem de Cem anos de solidão, de Gabriel García Márquez - Bondan, Gerusa (My University, 2014)
The subject of this dissertation is the analysis of the identity construction process of Amaranta, character of the book One Hundred Years of Solitude by Gabriel García Marquez. Aspects of the female identity related with woman representation and the fragmentation of the subject within the fantastic context of the book, as well as regional characteristics inside this perspective, are analyzed in this work. The structure of the present text is composed of several aspects, including the character corporality, the development of the double in her trajectory, her option for celibacy, the construction of motherhood, and the memory configuration during her old age. Studies about identity and culture, gender and feminist critics, and regionalism will be used as theoretical support for that analysis.
O tema da presente dissertação consiste na análise do processo de construção da identidade de Amaranta, personagem da obra Cem anos de solidão, de Gabriel García Márquez. Serão observados, nesse sentido, os aspectos relacionados à identidade feminina voltada à representação da mulher e à fragmentação do sujeito no contexto fantástico da obra, assim como na verificação da reprodução de noções de regionalidade dentro dessa perspectiva. A estrutura do trabalho é composta por aspectos como, corporalidade da personagem, desenvolvimento do duplo em sua trajetória, opção pelo celibato, construção da maternidade e configuração da memória na velhice. Para tanto, servirão como aporte teórico os estudos sobre identidade e cultura, gênero e crítica feminista, regionalidade.
Keywords: García Márquez, Gabriel; Cem anos de solidão (Obra literária); Literatura colombiana; Amaranta (Personagem fictício)